OPERATIONAL MANAGEMENT OF FISH AUCTION PLACE(TPI) AROUND MANDAILING DISTRICT, NORTH SUMATERA PROVINCE - Arismayani Siregar; Bustari Bustari; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in March 2019 at Fish Auction Place Natal Sekitar. The purpose of the research is to find out the operational management and the problems that exist in TPI Natal Sekitar, especially about the elements and the application of management functions in its management. The method used in this study is the survey method. Management data analysis was carried out descriptively. Based on the results of management research at TPI Natal Sekitar it has not been implemented well, because it has not been able to run the elements and functions of management as a whole in accordance with its provisions.Keywords: Operational Management , Fish Auction Place Natal Sekitar, Mandailing Natal District.